Sistem Pembelajaran Berbasis Website Quizpper untuk SMA Yayasan Mekar Arum - Youllia Indrawaty; Winarno Sugeng; Ivan Pakpahan; Rangga Bayu; Raden Akbar; Muhammad Faizal (Jurnal Pengabdian Masyarakat (ABDIRA), 2023)
This community service activity was carried out with the aim that the existing teaching and learning process at the Mekar Arum Foundation High School, Bandung Regency, West Java became more efficient and flexible. By providing an output in the form of an online learning website called Quizpper (quiz without paper), the Quizpper website is designed with the aim of improving the quality of teaching and learning activities between students and teachers in achieving learning objectives. Through the features available on the Quizpper learning website, the learning process also becomes more structured and organized, this is because Quizpper utilizes a database storage system. Design and development are carried out using the Research and Development (RD) method with a waterfall development model which consists of several stages, namely, requirements analysis, design, implementation or coding, and testing. The Quizpper website was developed using the PHP Codeigniter 3 framework and the mysql database as the storage tool. The arrangement and appearance of the front-end in the Quizpper learning system are adjusted based on teaching and learning activities in class.